MESSAGE FROM THE DESK OF THE EDITOR-IN-CHIEF - Dr Rana Al-Ghatam (Journal of the Bahrain Medical Society)
Dear Readers, We are delighted to present the December 2024 issue of JBMS, featuring impactful research and insights that advance medical knowledge. Your continued support has been instrumental in upholding the journal’s excellence and fostering growth.